Real estate principles - Jacobus, Charles J.
Completely updated, this best-selling principles book introduces the fundamentals of Real Estate unlike any other providing the user with a solid understanding of the real estate industry. Jacobus uses a readable yet authoritative approach making it a user-friendly resource for acquiring the knowledge to pass the licensing exam. As always, Jacobus highlights new and expanding concepts in the field of real estate, such as new Fannie Mae affordable housing programs, while continually reinforcing the more stable concepts that have been the cornerstone of American real estate ownership. Key chapters dealing with the financial aspects of real estate now include new information based on current changes and trends in the marketplace - variable rate commissions, government fiscal policy, investments, and income tax